Quantitative biokinetics of titanium dioxide nanoparticles after intratracheal instillation in rats: Part 3. Issue 4 (21st April 2017) - Kreyling, Wolfgang G.; Holzwarth, Uwe; Haberl, Nadine; Kozempel, Ján; Wenk, Alexander; Hirn, Stephanie; Schleh, Carsten; Schäffler, Martin; Lipka, Jens; Semmler-Behnke, Manuela; Gibson, Neil
Abstract: The biokinetics of a size-selected fraction (70 nm median size) of commercially available and 48 V-radiolabeled [ 48 V]TiO2 nanoparticles has been investigated in healthy adult female Wistar-Kyoto rats at retention time-points of 1 h, 4 h, 24 h, 7 d and 28 d after intratracheal instillation of a single dose of an aqueous [ 48 V]TiO2 -nanoparticle suspension. A completely balanced quantitative biodistribution in all organs and tissues was obtained by applying typical [ 48 V]TiO2 -nanoparticle doses in the range of 40–240 μg·kg −1 bodyweight and making use of the high sensitivity of the radiotracer technique. The [ 48 V]TiO2 -nanoparticle content was corrected for residual blood retained in organs and tissues after exsanguination and for 48 V-ions not bound to TiO2 -nanoparticles. About 4% of the initial peripheral lung dose passed through the air-blood-barrier after 1 h and were retained mainly in the carcass (4%); 0.3% after 28 d. Highest organ fractions of [ 48 V]TiO2 -nanoparticles present in liver and kidneys remained constant (0.03%). [ 48 V]TiO2 -nanoparticles which entered across the gut epithelium following fast and long-term clearance from the lungs via larynx increased from 5 to 20% of all translocated/absorbed [ 48 V]TiO2 -nanoparticles. This contribution may account for 1/5 of the nanoparticle retention in some organs. After normalizing the fractions of retained [ 48 V]TiO2 -nanoparticles to the fraction that reached systemic circulation, the biodistribution was compared with the biodistributions determined after IV-injection (Part 1) and gavage (GAV) (Part 2). The biokinetics patterns after IT-instillation and GAV were similar but both were distinctly different from the pattern after intravenous injection disproving the latter to be a suitable surrogate of the former applications. Considering that chronic occupational inhalation of relatively biopersistent TiO2 -particles (including nanoparticles) and accumulation in secondary organs may pose long-term health risks, this issue should be scrutinized more comprehensively.